2008
DOI: 10.3386/w14297
|View full text |Cite
|
Sign up to set email alerts
|

School Nutrition Programs and the Incidence of Childhood Obesity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…Such evidence has motivated extensive research into a link between school-based child nutrition programmes and child overweight and obesity, which has yielded mixed conclusions (8)(9)(10)(11)(12)(13)(14) . Notably, two recent studies (using the same data set, the Early Childhood Longitudinal Study) applied advanced econometric techniques to longitudinal, individual-level observational data and both concluded that school lunches contributed to increased student weight between kindergarten and grade 5 (13,14) .…”
Section: Food Policy Food Assistance School Nutrition Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Such evidence has motivated extensive research into a link between school-based child nutrition programmes and child overweight and obesity, which has yielded mixed conclusions (8)(9)(10)(11)(12)(13)(14) . Notably, two recent studies (using the same data set, the Early Childhood Longitudinal Study) applied advanced econometric techniques to longitudinal, individual-level observational data and both concluded that school lunches contributed to increased student weight between kindergarten and grade 5 (13,14) .…”
Section: Food Policy Food Assistance School Nutrition Obesitymentioning
confidence: 99%
“…In 2004-5, a nationwide assessment commissioned by the USDA estimated that just 4-7 % of schools complied with all NSLP nutrition standards (6) . In 2009-10, a subsequent assessment indicated overall nutrition improvements; however, under half of elementary schools and less than one-quarter of secondary schools at the time of the evaluation were serving lunches that would meet new energy ceilings (implemented in 2012) (7) .Such evidence has motivated extensive research into a link between school-based child nutrition programmes and child overweight and obesity, which has yielded mixed conclusions (8)(9)(10)(11)(12)(13)(14) . Notably, two recent studies (using the same data set, the Early Childhood Longitudinal Study) applied advanced econometric techniques to longitudinal, individual-level observational data and both concluded that school lunches contributed to increased student weight between kindergarten and grade 5 (13,14) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gundersen and Kreider (2011) …nd a bene…cial, causal e¤ect of SNAP participation on food security after accounting for non-random selection and measurement error in reports of both SNAP participation and food insecurity. Schanzenbach (2009) and Millimet et al (2010) …nd a detrimental, causal e¤ect of NSLP participation on child obesity. Millimet et al (2010Millimet et al ( , 2012) obtain a bene…cial, causal e¤ect of SBP participation on child obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Schanzenbach (2009) and Millimet et al (2010) …nd a detrimental, causal e¤ect of NSLP participation on child obesity. Millimet et al (2010Millimet et al ( , 2012) obtain a bene…cial, causal e¤ect of SBP participation on child obesity. Private food assistance programs administered through the nationwide network of Feeding America are additional sources of food assistance for families (Fiese et al 2011).…”
Section: Introductionmentioning
confidence: 99%